Wireless dendrometer and environmental sensing system for tree growth monitoring - Erasmus, Christoper Stefan (Stellenbosch : Stellenbosch University, 2025)
Erasmus, C. S. 2025. Wireless Dendrometer and Environmental Sensing System for Tree Growth Monitoring. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/43a3a1de-75af-429e-acfe-1381b86680b2